Optimizing the Role of Schools and Teachers in Preventing Children from Coming into Conflict with the Law - Hilda, Hilda; Asriyani, Asriyani; Utami, Fidyah Faramita; Achmad, Andi Nurul Isnawidiawinarti (Universitas Negeri Gorontalo, 2025)
The Law on Juvenile Justice System states that a child in conflict with the law is a child who is 12 (twelve) years old, but not yet 18 (eighteen) years old who is suspected of committing a criminal offense. Indonesia has a good set of rules but is still considered ineffective in resolving cases of children in conflict with the law. This is due to many factors such as the lack of socialization and counseling regarding the regulations governing this matter. Currently, the role of schools, especially teachers in preventing children (students) in conflict with the law is very important, given the number of cases where the perpetrators are children. The method used in this activity is the socialization method, which aims to provide understanding to schools and teachers as educational institutions and educators whose results can be seen from an increase in teachers' understanding of efforts to prevent children in conflict with the law.